DIVUSI INOVASI DAN BUDAYA: PENGGUNAAN BATEE RANUP DALAM TRADISI MEU-UROH (STUDI KASUS DI DESA COT LAGAN KECAMATAN WOYLA KABUPATEN ACEH BARAT) - Rahma Hidayati; Reni Juliani; Nidar Nidar (Universitas Teuku Umar, 2018)
Aceh is a region rich in tradition. One of the traditions that continues to be practiced is the meandering tradition. But in practice this tradition has undergone innovation. The ancient traditions were carried out by bringing a meaningful message that has a high meaning and now this tradition is carried out by bringing a